Exploring the Process of Online Brand Advocacy: An In-depth Qualitative Study of Active Fashion Brand Advocates in Indonesia Online Marketplaces (Indian Journal of Management and Language (IJML), 2025)
Customers actively supporting a company or product online is known as online brand advocacy and is a crucial component of online marketing. From the standpoint of active fashion brand advocates in online marketplaces, little studies focused on the steps or processes of online brand advocacy. This study attempts to fill this knowledge gap by investigating the process of online brand advocacy through in-depth interviews with 15 active fashion brand supporters in Indonesia online marketplaces. There are four key stages of online brand advocacy: (1) the initial stages of learning about and using the product; (2) the stages of developing a favorable attitude and emotional connection with the brand; (3) the stages of actively sharing and promoting the brand; and (4) the stages of developing a strong brand advocacy and community. The research also revealed that the participants' reasons for online brand promotion varied, including social identification, personal interest, and reciprocity. The results add to our understanding of online brand advocacy by giving us insights into the process from the viewpoints of active fashion brand advocates in Indonesia online marketplaces.